1997
DOI: 10.1111/j.1651-2227.1997.tb18306.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors and neuromotor behaviour during the neonatal period

Abstract: Katz-Salamon M, Allert K, Bergstrom B-M, Ericsson K, Hesser U, Forssberg H. Perinatal risk factors and neuromotor behaviour during the neonatal period. Acta Pzdiatr 1997; Suppl419: 27-36. Stockholm. ISSN Preterm birth is associated with an increased risk for neurological handicaps. The purpose of the present study has been: to investigate the influence of perinatal risk factors on early neuromotor development during the neonatal period; to specify the neuromotor parameters particularly sensitive to perinatal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…The results of the neonatal assessments at 36 and 40 wk of gestation were presented elsewhere (17). As the number of VLBW infants taking part in the examination at 3 y of age was low (n = 133) the results of this motor examination were excluded from the present analysis.…”
Section: Subjectsmentioning
confidence: 99%
“…The results of the neonatal assessments at 36 and 40 wk of gestation were presented elsewhere (17). As the number of VLBW infants taking part in the examination at 3 y of age was low (n = 133) the results of this motor examination were excluded from the present analysis.…”
Section: Subjectsmentioning
confidence: 99%
“…Existem três grupos de indicadores de risco para déficit motor sendo eles: risco biológico onde são incluídos RN com peso de nascimento < 1500 gramas, idade gestacional < 32 semanas, ventilação mecânica por mais de 36 horas, hemorragia peri-intraventricular graus III e IV, anormalidades do tônus muscular, Apgar < 5 no 5 o minuto e infecções congênitas; risco estabelecido que são RN portadores de hidrocefalia, microcefalia, anormalidades cromossômicas, anormalidades músculo-esqueléticas, miopatias congênitas e infecção por HIV; e por último os RNs incluídos no grupo de risco sócio-ambiental aonde apresentam alto risco social, abuso materno de drogas e/ou álcool e anormalidades no estado comportamental 5,6 .…”
Section: Introductionunclassified
“…In the very immature infant, a new broncho‐pulmonary dysplasia, (BPD), related to early oxygen and ventilatory exposure with the first breath of life has been described (4,5). BPD and long periods of mechanical ventilation (MV) are associated with an increased neurodevelopmental morbidity suggesting that minimizing the development of BPD in this population could have positive effects on outcome (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Only 24% of the infants received MV from the beginning and 51% of infants received early CPAP. The low BPD rate (14%) and the positive correlation found between the duration of MV and a poor neurological outcome, suggested that CPAP contributed to a more desirable outcome (7,10). Van Marter et al recently compared two neonatal units and found the incidence of BPD to vary from 4% to 22% in infants born with birth weights <1500 grams (11).…”
Section: Introductionmentioning
confidence: 99%